Long-term topical corticosteroid use and risk of skin cancer: a systematic review - Ratib, Sonia; Burden-Teh, Esther; Leonardi-Bee, Jo; Harwood, Catherine; Bath-Hextall, Fiona (Lippincott, Williams & Wilkins, 2018)
Objective: The objective of this systematic review was to synthesize available research evidence to determine the risk of skin cancer in patients with long-term use of topical corticosteroids (TCS). Introduction: Topical corticosteroids are one of the most commonly prescribed medicines in dermatology and the mainstay of the treatment of atopic dermatitis and other skin conditions such as psoriasis. They are often required for months or years to control the disease and ultimately restore patients’ quality of life. In some patients, TCS may have a local immunosuppressive effect and theoretically increase the risk of skin cancer, whilst on the other hand TCS may decrease the risk of skin cancer in patients where TCS are used to treat inflammatory skin disease. To date, no systematic review has been performed to collate evidence on the effect of long-term TCS use on the risk of skin cancer. Inclusion criteria: This review considered studies that included people of all ages, genders and ethnicities, including HIV and transplant participants or participants with genetic diseases (for example, Gorlin-Goltz syndrome) This review considered studies that evaluated long-term use of topical corticosteroids. “Long-term” was defined as using TCS more than once a week for a month or longer. The review included cohort, cross-sectional and case-control observational studies exploring the association between the stated intervention and outcomes. The primary outcome measures of interest were: non-melanoma skin cancer (keratinocyte carcinoma), cutaneous squamous cell carcinoma (cSSC), basal cell carcinoma (BCC) or melanoma skin cancer. Genital and oral skin cancers are considered to be slightly different so we did not include them in this review. Methods: We performed a comprehensive search of MEDLINE, Embase and LILACS on November 9, 2017 to identify observational epidemiological studies assessing the association between long-term TCS use and skin cancer. We also searched EThOS at the British Library and three drug safety databases to identify unpublished work. The titles, abstracts and full text identified from the search were assessed independently by two authors against pre-specified inclusion/exclusion criteria. Methodological quality was not assessed as no articles were found which met the inclusion criteria. Data extraction was not possible as no articles were found which met the inclusion criteria. It was not possible to complete data synthesis as no articles were found which met the inclusion criteria. Results: A total of 1703 potentially relevant studies were identified following a comprehensive electronic search. After abstract and title screening, 51 full texts were assessed for eligibility criteria. Of these, no study met the inclusion criteria. No additional records were identified from searching unpublished literature. Conclusions: We did not find any studies that could help us establish if long-term TCS use is associated with skin cancer. Future research using primary care databases might give a better understanding regarding long-term use of TCS and skin cancer.